Investigating readmission rates for patients undergoing oncologic resection and endoprosthetic reconstruction for primary sarcomas and tumors involving bone. Issue 2 (23rd March 2022) - Lazarides, Alexander L.; Flamant, Etienne M.; Cullen, Mark M.; Ferlauto, Harrison R.; Cochrane, Niall; Gao, Junheng; Jung, Sin‐Ho; Visgauss, Julia D.; Brigman, Brian E.; Eward, William C.
Abstract: Background: Little is known about the drivers of readmission in patients undergoing Orthopaedic oncologic resection. The goal of this study was to identify factors independently associated with 90‐day readmission for patients undergoing oncologic resection and subsequent prosthetic reconstruction for primary tumors involving bone. Methods: This was a retrospective comparative cohort study of patients treated from 2008 to 2019 who underwent endoprosthetic reconstruction for a primary bone tumor or soft tissue tumor involving bone, as well as those who underwent a revision endoprosthetic reconstruction if the primary endoprosthetic reconstruction was performed for an oncologic resection. The primary outcome measure was unplanned 90‐day readmission. Results: A total of 149 patients were identified who underwent 191 surgeries were for a primary bone or soft tissue tumor. The 90‐day readmission rate was 28.3%. Female gender, depression, higher tumor grade, vascular reconstruction, longer procedure duration, longer length of stay (LOS), multiple surgeries during an admission and disposition to a Skilled Nursing Facility were associated with readmission ( p  < 0.05). In a multivariate analysis, female sex, higher tumor grade and longer procedure duration were independently associated with risk of readmission ( p  < 0.05). Conclusions: Readmission rates are high following endoprosthetic reconstruction for Orthopaedic oncologic resections. Further work is necessary to help minimize unplanned readmissions.